Spectroscopic studies of Ln(III) complexes with polyoxometalates in solids, and aqueous and non-aqueous solutions - Stefan Lis; Slawomir But; Andrzej M. Klonkowski; Beata Grobelna (International Journal of Photoenergy)
Chosen polyoxometalate (POM) anions and their lanthanide(III) complexes, LnPOM, have been synthesized and spectroscopically characterized in solid state, aqueous and non-aqueous solutions. POMs, such as Keggin's, Dawson's and Anderson's type, Na9EuW10O36, compositions that function as inorganic cryptands ([(Na)P5W30O110]14−-Preyssler anion, and [(Na)As4W40O140]27−), containing inorganic (Na+,K+,NH4+) or organic (tetrabutylammonium, NBu4+) counter cations were obtained and their Ln(III) complexes (sandwiched and encapsulated) studied. The synthesized compounds were identified using elemental and thermogravimetric analysis, UV-Vis spectrophotometry and FTIR spectroscopy. The complexation studies were carried out with the use Nd(III) and Er(III) optical absorption and Eu(III) luminescence spectroscopy. Luminescence characterization, including results of intensity, quantum yields and luminescence lifetimes of EuPOM complexes in aqueous, non-aqueous solutions (DMF, DMSO, acetonitryle) and solid are discussed. Based on luminescence lifetime measurements of the Eu(III) ion the hydration numbers of its sandwiched (efficient emitters) and encrypted complexes have been determined and quenching effect discussed. The Eu(III) complexes entrapped in a xerogel matrix have been studied as luminescent materials. Luminescence intensity, lifetime and quantum yield of the EuPOM materials and their photochemical stability, during continuous UV irradiation, were tested.